Educação em Ciências Naturais no currículo de cursos de Pedagogia de universidades públicas federais na Amazônia Legal Brasileira - Batista, Eliane Regina Martins (2017)
This thesis presents the results of a study oriented by the proposal of analyzing the role of Education in Natural Sciences in the Curriculum of the Course of Pedagogy in the Public Federal Universities of the Brazilian Amazon Region. The adopted theoreticalmethodological references are based on the approach of cycle of policies that is, at the same time, a theoretical conception of policy and a method of research. The analyses are based upon the understanding that the curriculum policies are produced in a practical context, in this case, in the Public Federal Universities of the Brazilian Amazon Region, are connected to complex processes of production of policies in different spaces and epochs, notably in the context of influence and production of official texts that comprise the educational legislation. Under this theoretical-methodological assumption, these texts have been submitted to analyses in order to identify the relations between the selected Course Political Pedagogical Projects (PPCs) and the policies that are concerned with national and international contexts. This research tried to identify the proximities and distances between documents produced by UNESCO and OECD as the recommendations for Education in a general character, documents that establish the policies for the Brazilian Education System (National Guidelines for the Formation of Basic Education Teachers and the Professors of Pedagogy), as well as the Pedagogy PPCs in seven public federal universities in the Brazilian Amazon region. The analyses were organized in three axes: 1. General Characterization of the Pedagogy Courses in the Amazon region nowadays; 2. Curriculum principles that rule the formation of pedagogues in the selected investigated institutions; and 3. The importance of the studies related to Natural Sciences in the Pedagogy Course Curriculum. The results indicate that the proximities make remarkable references to the fundaments of formation of pedagogues for the teaching process, under a broad conception that also includes the preparation for school management and research issues, and for the actuation in technical duties in and out of schools as well. They also refer to the curriculum organization based on principles such as: theoretical-practical relations; interdisciplinary issues; competences and contextualization. The singularities were related with the organization of the curriculum and with the differences of senses that are attributed to the terms that compose the lexical of the educational policies, as an example of competence. As for the formation of pedagogues for the Teaching of Natural Sciences, the analyses point out for the differences in the academic subject nomenclature, course lengths and the position it takes in curriculum of all the other courses, as well as the predominance of the idea about curriculum as a collection of knowledge that are validated for modern Sciences. However, it is possible to visualize a proposal that favor the analyses between the relations of Sciences and life. It must be observed that cultural knowledge from the Brazilian Amazonian people were not included in the course contents. Based on the results of this study, some recommendations point out for the necessity of considering that the crisis of legitimation by which Science is on course has implications in the Curriculum. This does not mean to deny the importance of Science, but to question the idea of curriculum as a collection of pre-established knowledge as the best and unquestionable one. To end up, it is recommended that there must be a dialogue between the Formation for Teaching of Natural Sciences and the Amazonian peoples’ cultural knowledge. The Amazonian inhabitants understands nature very well, specially the language of waters, considering that in this region “rivers commands all living circumstances”. In summary, these analyses do not allow any debate towards the homogeneity around the formation of Natural Sciences teachers, indicating the practices of recontextualization by hybridisms.